The Determinants of Tourist Visiting Interest in Sade Village Tourism Central Lombok - Setiawan Bin Lahuri; Sri Firda Rahmi Aliya Putri; Devid Frastiawan Amir Sup; Muhammad Aunurrochim Mas'ad Saleh (Faculty of Islamic Economics and Business of Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Non Index Publication (Tier 4)